Electromagnetic field correlations and sound waves - Sokolovsky, A.I.; Stupka, A.A. (Вопросы атомной науки и техники, 2007)
Statistical operator of the many component plasma has been found on the basis of the Bogolyubov reduced description method and quasi-relativistic quantum electrodynamics. Calculations were carried out in the Hamilton gauge up to the second order of a perturbation theory in interaction. Closed system of equations for binary correlations of electromagnetic field and hydrodynamic variables of medium has been obtained and investigated near equilibrium. Classical Maxwell plasma approximation was studied. Coupled states of sound waves and waves of transversal correlation of the field were predicted. Waves of correlations of electromagnetic field can be excited by sound waves in plasma.